1981
DOI: 10.1210/jcem-52-5-903
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma and Urinary Dopamine during Dietary Sodium Depletion in Man*

Abstract: This study was designed to investigate the influence of dietary sodium restriction on plasma and urine dopamine levels. Five normal white male volunteer subjects wee studied in metabolic balance at constant 150 meq sodium, 60 meq potassium intake and then daily for 7 days on an isocaloric constant diet of 10 meq sodium and 60 meq potassium/day. With dietary sodium restriction, urinary sodium excretion decreased from 152 +/- 13 meq/day in stepwise fashion to 7 +/- 1 meq/day (P less than 0.001) on day 7. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 17 publications
2
18
2
Order By: Relevance
“…Conversely, sodium loading increases urinary dopamine levels (31). The mechanism for this increased dopamine excretion has been attributed to increased DOPA concentrations in plasma and tubular lumen (46) and increased proximal tubule DOPA uptake via a sodium-dependent cotransport process (44). Therefore, volume expansion may serve to decrease proximal tubule AT 1 receptor expression by decreasing local and/or systemic angiotensin II production and increasing proximal tubule dopamine production.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, sodium loading increases urinary dopamine levels (31). The mechanism for this increased dopamine excretion has been attributed to increased DOPA concentrations in plasma and tubular lumen (46) and increased proximal tubule DOPA uptake via a sodium-dependent cotransport process (44). Therefore, volume expansion may serve to decrease proximal tubule AT 1 receptor expression by decreasing local and/or systemic angiotensin II production and increasing proximal tubule dopamine production.…”
Section: Discussionmentioning
confidence: 99%
“…In normal humans, urinary dopamine excretion is increased during sodium loading and, conversely, is decreased during sodium depletion. 4 ' 5 Exogenous administration of dopamine in sodium-replete humans produces renal vasodilation and increases urinary sodium excretion. 6 In experimental animals, blockade of the renal DA, receptor impairs the natriuretic response to acute sodium load and produces antinatriuresis by a renal tubular mechanism.…”
mentioning
confidence: 99%
“…33 However, in our study we could not demonstrate any beneficial effect on BP that Comparative studies between different variables could be reliably related to breast feeding, a result that although not consensual, is in agreement with The comparative study between haptoglobin phenotypes, showed that allele 1 carriers had significantly other authors. 34,35 In addition, the intake of the main nutrients, such as sodium, potassium and calcium lower plasma renin and urine aldosterone and cAMP concentrations than allele 2, but dopamine per se, did not appear to influence in any significant tor with renal origin) 37,38 was observed (Table 3). These findings suggest that a sodium sensitive tendency is already present at the age of 12 months.…”
Section: Discussionmentioning
confidence: 96%